Relationship Between Birth Length, Parenting Practices, and Environmental Sanitation with Stunting in Children - Sulastri, Eni; Sari, Lutfiana Puspita; Solenda, Elvira Ardestin (Poltekkes Kemenkes Palembang, 2025)
Stunting is a condition of impaired growth and development in children resulting from chronic malnutrition, and it is influenced by various factors both before and after birth. This study aimed to examine the relationship between birth length, parenting patterns, and environmental sanitation with stunting among children aged 2–5 years in Klakah Village, Selo, Boyolali. A quantitative approach with a cross-sectional design was used. A total of 63 children were selected using purposive sampling. Data were collected through questionnaires and documentation, then analyzed using the Chi-Square test. The results showed no significant relationship between birth length and stunting (p > 0.05). However, there was a significant relationship between parenting patterns in feeding practices and environmental sanitation with stunting (p < 0.05). It can be concluded that stunting among children is more strongly associated with parenting practices and environmental conditions than with birth length. These findings are expected to serve as a basis for designing stunting prevention interventions that focus on family behavior and environmental improvements.